What Matters? The Valued Life Activities of Older Adults Undergoing Elective Surgery - Kata, Anna (J Am Geriatr Soc, 2019)
BACKGROUND/OBJECTIVES: Valued life activities are activities an individual deems particularly important or meaningful. Surgery in older adults can affect their ability to perform valued activities, but data are lacking. We characterized these activities and assessed performance of them following surgery. DESIGN: Retrospective observational study. SETTING: Preoperative program for older adults undergoing elective surgery at an academic hospital. PARTICIPANTS: Older adults (N=194) in the program from 2/2015 to 2/2018. MEASUREMENTS: Preoperative written questionnaire asked, “What are the activities that are most important to you to be able to do when you return home from surgery?” Participants could list up to three activities. Content analysis was used to develop domains of valued life activities and categorize responses. Postoperative questionnaires and medical records were used to determine ability to perform activities six months after surgery. RESULTS: Of 194 participants (mean age 74.9 ± 9.1 years), 57.7% were female, 33.5% had more than two comorbid conditions. We elicited 510 valued activities, with a mean of 2.6 (± 0.7) activities per participant. Content analysis revealed five categories: 1) recreational activities (28.9%); 2) mobility (24.9%); 3) activities of daily living (ADLs, 17.5%); 4) instrumental activities of daily living (IADLs, 16.9%); and 5) social activities (12.0%). Ultimately, 154 participants had surgery, of which 27.3% were unable to perform one of their valued activities at six months. Performance varied between activity categories; 91.9% of mobility activities, 90.8% of ADLs, 80.3% of IADLs, 77.3% of social activities, and 65.5% of recreational activities were able to be performed after surgery. CONCLUSION: Older adults expressed a wide range of valued life activities. Over a quarter were unable to engage in at least one valued life activity after surgery, with recreation being the most commonly affected. Assessment of valued life activities should be incorporated into the perioperative management of older adults.